The Moral Intelligence of the Worker and Its Impact on the Organizational Prowess: An Exploratory Study of the Opinions of a Sample of Kufa Cement Plant Workers - Kadim, Jasim Rahi; Sabti, Yousif Mousa; Ali, Ghazanfar; Rizvi, Tamkinut; Shaltag, Karim Hazen; Abbas, Yasir Abdullah; Karim, Hussein Youssef; Shliot, Sadeq Mehdi (South Asian Journal of Social Sciences and Humanities, 2021)
This research aims to identify the impact of the moral intelligence of the worker in its dimensions (sympathy, conscience, self-censorship) in enhancing the organizational prowess in its dimensions represented by (exploring opportunities, exploiting opportunities, flexibility at work) in the Kufa cement factory, as the research problem lies in the extent of interest. In addition to the relationship between them, the importance of research is highlighted in diagnosing the impact of moral intelligence of the worker in its dimensions in enhancing organizational skill in its dimensions, and in order to achieve the goal of the research, a sample of workers in the Kufa cement plant was selected and the researcher relied on the questionnaire as a tool to collect the necessary data and in order to complete the research and achieve the objectives it seeks, (144) questionnaires were distributed, the researcher obtained (140) a questionnaire valid for statistical analysis, and the research included two hypotheses, the statistical program (SPSS v. 23) was used, and the research reached a set of conclusions. The ingenuity generally represents the extent of control and effectiveness of smart organizations in their development process in order to reach advanced ranks of advancement and progress, with a basic ability that requires exploration and exploitation of available opportunities and work to reduce difficulties, threats and disposal Ones at work.
Keywords: Moral intelligence; organizational prowess; exploitation; Kufa cement plant